Internationalization and capital structures empirical evidence : from Malaysia public listed manufacturing firms / Arison Ho Sel Chuan - Ho, Arison Sel Chuan (2013)
This investigation attempts to examine the determinants of capital structure for internationalized manufacturing firms that are listed on Bursa Malaysia. Firm-related characteristic variables namely internationalization, firm size, profitability, company growth and tangibility over period 2007-2011 are tested their relationship with debt ratio of firms by using panel data with under Pooled OLS and Fixed Effects Model. The results showed that firm size and tangibility are significantly positively related with debt ratio while internationalization, profitability and company growth are significantly inversely related with debt ratio. The findings indicate that the static trade-off theory, pecking-order theory and agency theory are pertinent in Malaysia situation.